Progressive Skeletal Muscle Loss After Surgery and Adjuvant Radiotherapy Impact Survival Outcomes in Patients With Early Stage Cervical Cancer - Lee, Jie; Lin, Jhen-Bin; Chen, Tze-Chien; Jan, Ya-Ting; Sun, Fang-Ju; Chen, Yu-Jen; Wu, Meng-Hao (Frontiers in Nutrition, 2022)
The effect of skeletal muscle loss associated with surgery and adjuvant radiotherapy on survival outcomes in patients with early-stage cervical cancer remains unclear. We analyzed the data of 133 patients with early-stage cervical cancer who underwent surgery and adjuvant radiotherapy between 2013 and 2018 at two tertiary centers. Skeletal muscle changes were measured using computed tomography scans at baseline, at simulation for radiotherapy, and at 3 months post-treatment. A decrease of ≥5% in the skeletal muscle was defined as “muscle loss.” The Patient-Reported Outcome version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) was used to assess gastrointestinal toxicity. The Patient-Generated Subjective Global Assessment (PG-SGA) was used for nutritional assessment. Predictors of overall survival were identified using the Cox regression models. The median follow-up period was 3.7 years. After treatment, 32 patients (24.1%) experienced muscle loss. The rate of muscle loss was higher in patients with PRO-CTCAE score ≥3 or PG-SGA score ≥4 at the end of radiotherapy than in patients with PRO-CTCAE score ≤2 or PG-SGA score 0–3 (75.0% vs. 10.5%, p<0.001; 71.4% vs. 2.2%, p<0.001). The 3-year overall survival was significantly lower in patients with muscle loss than in those with muscle preserved (65.6% vs. 93.9%, p<0.001). Multivariate analysis showed that muscle loss was independently associated with poor overall survival (hazard ratio, 4.55; 95% confidence interval: 1.63–12.72; p<0.001). Muscle loss after surgery and adjuvant radiotherapy was associated with poor overall survival in patients with early-stage cervical cancer. Muscle loss is associated with patient-reported gastrointestinal toxicity and deterioration in nutritional status.